Plasmonic Core/Satellite Heterostructure with Hierarchical Nanogaps for Raman Spectroscopy Enhanced by Shell‐Isolated Nanoparticles. Issue 8 (19th May 2014) - He, Ru; Cheng, Yuchuan; Jin, Ting; Jiang, Meng; Chen, Chao; Xu, Gaojie
<x xml:space="preserve">Abstract</x> A plasmonic core/satellite heterostructure is synthesized through an electrostatic self‐assembly protocol. The heterostructure comprises C‐coated Ag nanoparticles known as Ag@C shell‐isolated nanoparticles (SHINs) acting as satellite particles and a C‐coated Fe3O4 dielectric particle core (Fe3O4@C). The enhanced electromagnetic field generated from the hierarchical nanoscale gaps found among the particles makes high‐quality Raman spectra possible. As a result, shell‐isolated‐nanoparticle‐enhanced Raman spectroscopy (SHINERS) based on this heterostructure is successfully applied for in‐situ trace‐amount detection of perylene in water. There is potential for its use in ultrasensitive detection in the liquid phase with real‐time monitoring. This work offers a new strategy for developing SHINs to improve the performance of SHINERS.